Interpretation of gravity data to delineate the geothermal reservoir extent and assess the geothermal resource from low-temperature fluids in the Municipality of Isa, Southern Kyushu, Japan. (January 2020) - Pocasangre, Carlos; Fujimitsu, Yasuhiro; Nishijima, Jun
Highlights: The municipality of Isa is located in the southern part of Kyushu Island. The study attempts to analyze and interpret the gravity data. An area of 10 × 10 km was analyzed considering a Bouguer Density of 2.46 g/cm 3 . The probable geothermal reserve has an area of 4.006 km 2 . The geothermal power potential is greater than or equal to 121.9 kWe. Abstract: The municipality of Isa is located in the southern part of Kyushu Island, and it is considered one of the wealthiest places in Japan because of the existence of precious minerals. This study attempts to analyze and interpret the gravity data for delineating the geothermal reservoir boundary and the assessment of geothermal resource. Accordingly, the corresponding authors selected an area of 10 × 10 km and analyzed considering a Bouguer Density of 2.46 g/cm 3 . The Bouguer Anomaly result shows a high value at the center, which extends 5.61 km 2 . The 2-D gravity inversion was carried out and the profiles showed the depth of the Shimanto Supergroup. Also, the authors carried out 3-D gravity modeling. The result shows an area which has density values below 2.40 g/cm 3 and the zone of NE-SW direction that starts at the Uonogoe area and ends at the Yamada area. Besides, a large anomaly located in the central area that has density values above 2.50 g/cm 3 is evident. This anomaly represents the hydrothermal alteration zone that hosts the propylitic altered rocks having precious minerals. Between these evidenced zones, we could infer the location of the probable geothermal reserve which has an area of 4.006 km 2 . Integrating past research results, using the volumetric method, and a Monte Carlo simulation, we estimated with 90% of confidence the geothermal power potential, which is greater than or equal to 4.27 MWe and 121.9 kWe for the inferred and probable geothermal resource respectively for 20 years.